Composição e abundância da ictiofauna na zona litorânea de um tributário, na zona de sua desembocadura no reservatório de Jurumirim, Estado de São Paulo, Brasil - De Castro, Reinaldo José [UNESP]; Foresti, Fausto [UNESP]; Carvalho, Edmir Daniel [UNESP] (Universidade Estadual de Maringa, 2003)
Monthly collections of fishes using a trawl net were carried out from August 1996 to December 1997 with the objective of evaluating the composition and diversity of fish species in the littoral area of the transition zone between Veados Stream and Jurumirim Dam (Upper Paranapanema River, São Paulo State). Diversity and similarity indices of ichthyofauna at the sites were determined and correlated with abiotic factors such as dissolved oxygen, temperature, pluviometric precipitation and hydrological level. Twenty-six (26) fish species (the majority small-sized) of the family Characidae (Tetragonopterinae and Cheirodontinae) were registered. Representatives of the orders Siluformes, Gymnotiformes, Perciformes and Synbranchiformes occurred in lower abundance. Significant differences were found in the site diversity indices, but not in the abiotic factors. Significant correlations between the abundance of the ichthyofauna and the variations in the abiotic factors were not detected. The presence of fish larvae in the samples indicates the importance of the transition zone as a reproduction area of the fish species registered in this study.
Composition and abundance of ichthyofauna in the littoral zone of a tributary (mouth area) in Jurumirim reservoir (São Paulo state, Brazil)
Keywords: Abundance; Composition; Fishes; Jurumirim reservoir; Paranapanema River; dissolved oxygen; Brazil; breeding; fish; Gymnotiformes; intertidal zone; mouth; nonhuman; Perciformes; population abundance; reservoir; river; species composition; species diversity; temperature; trawl fishery; Characidae; Cheirodontinae; Pisces; Synbranchiformes; Tetragonopterinae